Treatment of partial injury of the calcaneus tendon with heterologous fibrin biopolymer and/or photobiomodulation in rats - de Freitas Dutra Júnior, Enéas; Hidd, Sílvia Maria Cardoso Magalhães; Amaral, Marcello Magri; Filho, Antonio Luiz Martins Maia; Assis, Livia; Ferreira, Rui Seabra [UNESP]; Barraviera, Benedito [UNESP]; Martignago, Cintia Cristina Santi; Figueredo-Silva, José; de Oliveira, Rauirys Alencar; Tim, Carla Roberta (Springer Nature, 2021)
The present study aimed to evaluate the new heterologous fibrin biopolymer associated, or not, with photobiomodulation therapy for application in tendon injuries, considered a serious and common orthopedic problem. Thus, 84 Rattus norvegicus had partial transection of the calcaneus tendon (PTCT) and were randomly divided into: control (CG); heterologous fibrin biopolymer (HFB); photobiomodulation (PBM); heterologous fibrin biopolymer + photobiomodulation (HFB + PBM). The animals received HFB immediately after PTCT, while PBM (660 nm, 40 mW, 0.23 J) started 24 h post injury and followed every 24 h for 7, 14, and 21 days. The results of the edema volume showed that after 24 h of PTCT, there was no statistical difference among the groups. After 7, 14, and 21 days, it was observed that the treatment groups were effective in reducing edema when compared to the control. The HFB had the highest edema volume reduction after 21 days of treatment. The treatment groups did not induce tissue necrosis or infections on the histopathological analysis. Tenocyte proliferation, granulation tissue, and collagen formation were observed in the PTCT area in the HFB and HFB + PBM groups, which culminated a better repair process when compared to the CG in the 3 experimental periods. Interestingly, the PBM group revealed, in histological analysis, major tendon injury after 7 days; however, in the periods of 14 and 21 days, the PBM had a better repair process compared to the CG. In the quantification of collagen, there was no statistical difference between the groups in the 3 experimental periods. The findings suggest that the HFB and PBM treatments, isolated or associated, were effective in reducing the volume of the edema, stimulating the repair process. However, the use of HFB alone was more effective in promoting the tendon repair process. Thus, the present study consolidates previous studies of tendon repair with this new HFB. Future clinical trials will be needed to validate this proposal.
Keywords: Calcaneus tendon; Heterologous fibrin biopolymer; Photobiomodulation; Rats; Tissue repair